Exploring the Study Habits of Expert Language Learners - Tapia, Norma; Castillo, Maria; Tornés, Nora (CIEX JOURNAL, 2017)
The main goal of this research, developed in a private language center in southern Mexico, is to explore the study habits that expert language learners use to learn English. The literature review analyses concepts such as: study habits, expert language learners and language learning. The research instrument is a questionnaire which aim was to explore the actions that expert language learners take in order to be successful. The findings were classified in the categories: environmental factors, emotional and physical health, study method, time organization, exams, and motivation, taken from Oñade, C. (1991).